The impact of hippocampal damage on appetitive control. Issue 5 (2nd September 2020) - Zuniga, Andrea; J. Stevenson, Richard; C. Thayer, Zoe; A. Miller, Laurie; M. Francis, Heather; Saluja, Supreet; Nikpour, Armin
ABSTRACT: Animal data indicates the hippocampus assists appetite-regulation. We tested this in humans, contrasting two patients (DW, JC) with hippocampal damage to controls on an appetite-regulation test conducted hungry and sated. When hungry, controls viewed palatable snacks and reported a desire to eat them, a memory-based judgment. After sampling them, they reported liking their taste. Post-lunch (DW ate little, precluding a test of our hypothesis), controls showed a large decrease in desire for the snacks, but less change in taste-liking. JC ate like controls, but reported no change in desire across states, suggesting that the human hippocampus also contributes to appetite-regulation.